The Winning Spirit (California : Griffin Publishing, 1996)
The U.S. Special Olympics skaters are going to pair up with the Silver Blades in a mini-competition.
RL:5.0.
009-012.
Keywords: Skating -- Juvenile fiction; Competition (Psychology) -- Juvenile fiction; Skating -- Fiction; Young adult fiction